Enhancement of Metabolite Production in High-Altitude Microalgal Strains by Optimized C/N/P Ratio (2022)
: This study evaluated the role of C/N/P in the increase in the synthesis of carbohydrates, proteins, and lipids in two high-mountain strains of algae (Chlorella sp. UFPS019 and Desmodesmus sp. UFPS021). Three carbon sources (sodium acetate, sodium carbonate, and sodium bicarbonate), and the sources of nitrogen (NaNO3 ) and phosphate (KH2PO4 and K2HPO4 ) were analyzed using a surface response (3 factors, 2 levels). In Chlorella sp. UFPS019, the optimal conditions to enhance the synthesis of carbohydrates were high sodium carbonate content (3.53 g/L), high KH2PO4 and K2HPO4 content (0.06 and 0.14 g/L, respectively), and medium-high NaNO3 (0.1875 g/L). In the case of lipids, a high concentration of sodium acetate (1.19 g/L) coupled with high KH2PO4 and K2HPO4 content (0.056 and 0.131 g/L, respectively) and a low concentration of NaNO3 (0.075 g/L) drastically induced the synthesis of lipids. In the case of Desmodesmus sp. UFPS021, the protein content was increased using high sodium acetate (2 g/L), high KH2PO4 and K2HPO4 content (0.056 and 0.131 g/L, respectively), and high NaNO3 concentration (0.25 g/L). These results demonstrate that the correct adjustment of the C/N/P ratio can enhance the capacity of high-mountain strains of algae to produce high concentrations of carbohydrates, proteins, and lipids.